The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/2019.12.27.889089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles for rational Cas13d guide design

Abstract: AbstractType VI CRISPR enzymes have recently been identified as programmable RNA-guided, RNA-targeting Cas proteins with nuclease activity that allow for specific and robust target gene knock-down without altering the genome. However, we currently lack information about optimal Cas13 guide RNA designs for high target RNA knock-down efficacy. To close this gap, we conducted four massively-parallel Cas13 screens targeting the mRNA of a destabilized green fluorescent protein (GFP)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Optimization of gRNA design may further improve these systems as CasRx gRNAs have been shown to have variable knockdown efficiency. 5,53 Nevertheless, this is an important first step towards making transcriptome engineering a viable in vivo technology and provides a foundation for future experiments to mitigate the off-target and toxic attributes of the enzyme to make a new, viable tool in the expanding gene-editing toolbox.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of gRNA design may further improve these systems as CasRx gRNAs have been shown to have variable knockdown efficiency. 5,53 Nevertheless, this is an important first step towards making transcriptome engineering a viable in vivo technology and provides a foundation for future experiments to mitigate the off-target and toxic attributes of the enzyme to make a new, viable tool in the expanding gene-editing toolbox.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the phenotypes of y varied by their expression, with ubiquitous expression of CasRx resulting in a Ubiq-CasRx/+; gRNA y /+ lethal phenotype and embryo and wing and body specific expression mitigated lethality phenotype seen in Ubiq-CasRx expression. Optimization of gRNA design may further improve these systems as CasRx gRNAs have been shown to have variable knockdown efficiency [5,47]. Nevertheless, this is an important first step towards making transcriptome engineering a viable in vivo technology and provides a foundation for future experiments to mitigate the off-target and toxic attributes of the enzyme to make a new, viable tool in the expanding gene-editing toolbox.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of the one-vector system was also recently noted in an independent study 44 . To overcome this issue, we used two separate lentiviral vectors for dCas13d and gRNA expression, which were sequentially transduced into cells, similar to recent Cas13d-based knockdown screens published during the course of this study [42][43][44][45][46][47][48] . Another key issue that made dCas13d-based screening more challenging, compared to Cas13d-based knockdown screening, is likely the requirement for more stable binding of dCas13d/gRNA and target sites to effectively compete with cognate RNA-binding effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that gRNA length may affect the efficiency of Cas13d-mediated target RNA cleavage 42,45,47,56 . In our initial transfections, we used the 22-nt gRNA D [9,30] targeting the ISS-N1 region as a positive control segRNA.…”
Section: Specific Splicing Activation and Repression Through Transien...mentioning
confidence: 99%
See 1 more Smart Citation